The effect of limestone and bottom ash sand with recycled fine aggregate in foam concrete - Gencel, Osman; Balci, Bekir; Bayraktar, Oguzhan Yavuz; Nodehi, Mehrab; Sarı, Ahmet; Kaplan, Gökhan; Hekimoğlu, Gökhan; Gholampour, Aliakbar; Benli, Ahmet; Ozbakkaloglu, Togay (Elsevier BV, 2022)
To follow resource conservation, the production of optimized and sustainable structures through the use of insulating materials, such as foam concrete, has become a trend in construction industry. Although foam concrete has numerous benefits, the larger use of Portland cement in its mixture and its relatively low thermo-durability properties because of the low quantity of solid materials are of major concerns, challenging its large-scale applications. In that respect, this research evaluates the use of recycled fine concrete aggregate, limestone and bottom ash sand as the main aggregate materials to evaluate the physico-mechanical and thermo-durability properties of foam concrete. To that end, 25 mixes have been produced and a comprehensive series of tests including flowability, compressive and flexural strengths, water absorption, apparent porosity, drying shrinkage, sorptivity, abrasion resistance, thermal conductivity, along with the effect of elevated temperature and its respective cooling regime on foam concretes have been conducted in this study. The results show that foam concretes manufactured with bottom ash and recycled fine aggregates develop a considerably lower thermal conductivity values despite being outperformed in physico-mechanical properties by those mixes produced with limestone sand. Nonetheless, the inclusion of bottom ash sand is found to produce foam concretes with a comparable physico-mechanical and thermo-durability properties to mixes with limestone. The results of this study point to the suitability of utilizing alternative fine-sized aggregates, such as recycled fine aggregates along with bottom ash sand, in the production of foam concrete without compromising the insulating properties of the produced concrete.
Keywords: Physico-Mechanical Properties; Mechanics of Materials; Foam Concrete; Thermo-Durability Properties; Cooling Regime; Bottom Ash Sand